Project Based Learning Model Enhances Problem Solving Skills and Collaborative Abilities of Kindergarten Group B Children - Sari Dewi Astuti; Desak Putu Parmiti; Maria Goreti Rini Kristiantari (Journal of Education Action Reseach, 2025)
Several challenges were identified in the learning process, notably that 70% of students experienced difficulties working in groups or teams, indicating a lack of collaborative skills. Furthermore, only 20% of students actively participated in group activities, with the majority preferring to work independently. These deficiencies in problem solving and collaboration may negatively impact students’ academic achievement. This study aimed to analyze the implementation of Project-Based Learning (PBL) in improving the problem solving skills and collaborative abilities of kindergarten students in Group B. A quasi experimental method with a quantitative approach was employed. The research design utilized was the Posttest Only Control Group Design. The population of the study consisted of 120 Group B kindergarten students, with a total sample of 30 students selected through purposive sampling. Data were collected using observation methods, with an observation sheet serving as the primary instrument. The data analysis techniques included qualitative descriptive statistics, quantitative statistics, and Multivariate Analysis of Variance (MANOVA). The results of the study revealed a significant difference in the application of project based learning to students’ problem solving skills and collaborative abilities. The Pillai’s Trace value was 0.770, with a significance level of p < 0.05, indicating that the model had a strong and meaningful effect on both skill sets simultaneously. In conclusion, project based learning is demonstrated to be an effective and comprehensive instructional strategy for supporting the integrated development of problem solving and collaborative skills in kindergarten Group B students.